Effect of Bacillus subtilis IMV B-7023 on Wheat Growth, Photopigment Content in Leaves, and Gibberellins in Root Exudates - Vasyuk, V.A.; Chobotarova, V.V.; Parkhomenko, N.Y.; Chobotarov, A.Yu.; Kurdish, I.K.; Васюк, В.А.; Чоботарьова, В.В.; Пархоменко, Н.Й.; Чоботарьов, А.Ю.; Курдиш, І.К. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Root exudates of plants contain a significant number of organic compounds of various types, which influence the composition of plant microbiota that, in turn, has a substantial effect on their growth, development, and productivity. Among these compounds, gibberellins play an important role. The effect of Bacillus subtilis IMV B-7023 on gibberellin content in the plant growth zone has not been studied. The aim of this work was to determine the characteristics of the interaction between Bacillus subtilis IMV B-7023 — a component of the Azogran preparation — and wheat plants in terms of the production of gibberellin-like substances, their influence on plant growth, and the content of photopigments. Methods. Experiments were carried out on wheat of the Shestopalivka variety, the seeds of which were inoculated with suspensions of B. subtilis IMV B-7023. The plants were grown under sterile conditions in a phytotron using a hydroponic setup with Fahraeus medium for 14 days. Plant shoot length and root mass were measured. The content of photosynthetic pigments in the plant leaves was determined spectrophotometrically. Gibberellin-like substances in plant root exudates were identified using a biotesting method based on the stimulation of hypocotyl growth in lettuce (variety Kucheravyi Odeskyi). Results. Inoculation of wheat seeds with B. subtilis IMV B-7023 significantly improved plant growth and the accumulation of chlorophylls a and b, as well as carotenoids, in the leaves. When plants were grown from inoculated seeds in solution, the gibberellin content increased significantly. Conclusions. Inoculating wheat seeds stimulates plant growth under hydroponic conditions and increases the content of photosynthetic pigments — chlorophylls a and b, and carotenoids — in the leaves. Under such conditions, gibberellin levels in the plant growth medium increased by 141–283% compared to the control.